High oxygen barrier materials from paper to regenerated cellulose films. Issue 1 (6th October 2022) - Jiang, Baoqiang; Tang, Yali; Zhou, Keke; Lu, Lixin; Qiu, Xiaolin; Pan, Liao
Abstract: A transparent, bendable, high oxygen barrier cellulose‐based film was prepared, which has far better oxygen barrier properties than conventional polyethylene, polypropylene and cellophane materials. A series of regenerated cellulose films (RCs) were prepared from filter paper lacking oxygen barrier properties under different cellulose concentrations and gelation times. It was shown that the cellulose concentration and gel time had a greater effect on the oxygen barrier properties of RCs. When the cellulose concentration was 4 wt% and the gel time was 3 h, the RCs obtained the lowest oxygen permeability coefficient (OPC) down to 2.21 × 10 −17 cm 3 cm cm −2 s −1 Pa −1 . The films have a tensile strength of 109.5 MPa, an elongation at break of 27.3% and a light transmission rate of 89%. In further, molecular dynamics simulations showed that when the filter paper was converted to RCs, the increase in hydrogen bonding and the decrease in free volume between cellulose chains caused a decrease in the diffusion coefficient of oxygen. As a novel biobased high oxygen barrier material, the film has broad application prospect in packaging and chemical industry. Abstract : High oxygen barrier regenerated cellulose films were prepared directly from filter paper. The oxygen barrier, tensile strength, and light transmission were affected by using different cellulose solution concentrations and gelation times. When the cellulose concentration was 4 wt% and the gel time was 3 h, the RCs obtained the lowest oxygen permeability coefficient down to 2.21 × 10 −17 cm 3 cm cm −2 s −1 Pa −1 .